Automated wide-line nuclear quadrupole resonance of mixed-cation lead-halide perovskites - J. W. Wolffs; J. S. Gómez; G. E. Janssen; G. A. de Wijs; A. P. M. Kentgens (Magnetic Resonance)
Nuclear quadrupole resonance (NQR), a technique related to nuclear magnetic resonance, is extremely sensitive to local crystal composition and structure. Unfortunately, in disordered materials, this sensitivity also leads to very large linewidths, presenting a technical challenge and requiring a serious time investment to get a full spectrum. Here, we describe our newly developed, automated NQR set-up to acquire high-quality wide-line spectra. Using this set-up, we carried out 127I NQR on three mixed-cation lead-halide perovskites (LHPs) of the form MAxFA1−xPbI3 (where MA denotes methylammonium; FA denotes formamidinium; and x = 0.25, 0.50 and 0.75) at various temperatures. We achieve a signal-to-noise ratio of up to ∼ 400 for lineshapes with a full width at half maximum of ∼ 2.5 MHz acquired with a spectral width of 20 MHz in the course of 2–3 d. The spectra, which at least partially exhibit features encoding structural information, are interpreted using a statistical model. This model finds a degree of MA–MA and FA–FA clustering (0.2<mspace linebreak="nobreak" width="0.125em"/>≤<mspace width="0.125em" linebreak="nobreak"/>S<mspace width="0.125em" linebreak="nobreak"/>≤<mspace linebreak="nobreak" width="0.125em"/>0.35<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="77pt" height="11pt" class="svg-formula" dspmath="mathimg" md5hash="3a87b1914cc7526b85faf97a713928fc"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="mr-6-143-2025-ie00001.svg" width="77pt" height="11pt" src="mr-6-143-2025-ie00001.png"/></svg:svg>). This proof-of-principle for both the wide-line NQR set-up and the statistical model widens the applicability of an underutilised avenue of non-invasive structural research.